The Influence of the Use of Educational Technology on the Quality of Learning at Public Elementary Schools - Yelli Ari Subekti; Widya Kusumaningsih; I Made Sudana (Lembaran Ilmu Kependidikan, 2025)
Background - The development of digital technology has brought significant changes to the field of education, especially in the learning process at the elementary school level. The use of educational technology has become an important strategy to improve learning quality, student engagement, and the effectiveness of content delivery. However, not all educational institutions, particularly in rural areas, have optimally integrated technology into the learning process. Therefore, it is essential to examine the extent to which the use of educational technology affects the quality of learning, particularly in public elementary schools in the Randublatung District. Purpose - This study aims to investigate the impact of using educational technology on the quality of learning at public elementary schools in Randublatung District. This research uses a quantitative approach with a descriptive analysis design. Data were collected through questionnaires distributed to teachers and students and analyzed using statistical techniques to examine the relationships between variables. Findings - The results show that the use of educational technology contributes significantly and positively to the improvement of learning quality, with an influence value of 82.4%. Technology integration has been proven to enhance student interaction and engagement and support the overall success of the teaching and learning process. Conclusions - The study concludes that the use of educational technology plays a crucial role in improving the quality of learning. Systematic adoption and training in technology use within the educational environment are necessary to achieve more effective and higher-quality learning outcomes. Novelty/Originality/Value The novelty of this research lies in its empirical evidence showing the substantial contribution of educational technology to learning quality in elementary schools located in rural areas, specifically in Randublatung. Furthermore, the study highlights the importance of onboarding training for users (teachers and students) as a key factor in the successful integration of technology in education—an aspect rarely discussed in previous similar studies.